Pengaruh Pendidikan Kesehatan Tentang Kejang Demam Terhadap Peningkatan Keterampilan Ibu Dalam Memberikan Pertolongan Pertama Pada Anak Kejang Demam Di Desa Blukon Kabupaten Lumajang - Widiyanto Widiyanto; Mariani Mariani; Marfuah Marfuah (Pusat Riset dan Inovasi Nasional, 2023)
Febrile seizures are one of the manifestations of health problems that often occur in children aged three months to 5 years and can potentially cause harmful complications in children. Complications of febrile seizures occur due to a lack of parental skills in providing proper first aid to children with febrile seizures. Health education about febrile seizures is thought to improve parents' skills in performing first aid measures for children with febrile seizures. This study aims to explain the effect of health education about febrile seizures on increasing the skills of mothers in providing first aid to children with febrile seizures.This study uses a quasi-experimental design with a one-group pre-posttest design without a control. The samples involved in this study were mothers with children aged three months - 5 years in Blukon Village, Lumajang District, who met the inclusion and exclusion criteria determined by the researchers with a total of 48 people. The intervention applied in this study was providing health education about febrile seizures. Data collection used observation sheets as a checklist for first aid management in children with febrile seizures, carried out before and after the intervention. Data were analyzed using the Wilcoxon signed rank test with the help of IBM SPSS 25 software.The pre-test results showed that the mean ± SD of the mother's skill in performing first aid for children with febrile seizures was 2.41 ± 0.84. The mean ± SD score of mothers' skills in providing first aid to children with seizures increased after attending health education about febrile seizures to 6.47 ± 0.68. The results of data analysis showed that the provision of health education about febrile seizures had a significant effect on increasing the skills of mothers in performing first aid for children with febrile seizures with a ρ-value = 0.000 or less than 0.05.In controlling patterns of delivering health education about febrile seizures, this research calls for increased effort and assistance from local health workers. First aid procedures for children experiencing febrile seizures will become more instinctive or skillful when understanding is followed by frequent demonstrations. .